Antioxidant and Cytotoxic Activity of New Polyphenolic Derivatives of Quinazolin-4(3H)-one: Synthesis and In Vitro Activities Evaluation - Raluca Pele; Gabriel Marc; Ioana Ionuț; Cristina Nastasă; Ionel Fizeșan; Adrian Pîrnău; Laurian Vlase; Mariana Palage; Smaranda Oniga; Ovidiu Oniga (MDPI AG, 2022)
The development of hybrid molecules with significant human therapeutic properties is one of the main approaches of pharmaceutical research. One of the most important pharmacophores is the quinazolin-4(3H)-one heterocycle moiety, due to its wide range of biological activities. By its derivatization with polyphenolic compounds, in our previous research, it proved to possess a good antiradical activity of ortho-diphenolic derivatives of quinazolin-4(3H)-one. In this study, we developed two new series of compounds, with an additional phenolic group or with a methyl group on the thioacetohydrazone fragment. The methods used to evaluate the activity of the compounds were radical scavenging, reduction of oxidizing reagents and transition metals' ions chelation assays. Quantum descriptors were also calculated in order to evaluate the influence of substituents and their position on the activity of the compounds. The cytotoxic activity was evaluated using normal human foreskin fibroblast cells (BJ) and two cancerous cell lines, lung adenocarcinoma cells (A549) and prostate carcinoma cells (LNCaP). The results obtained for the pyrogallol derivatives showed a high antioxidant activity compared to ascorbic acid and Trolox. All the synthesized compounds displayed a higher cytotoxicity against the cancerous cell types and a high cytocompatibility with the normal cells. The antioxidant activity was deeply influenced by the addition of the third phenolic group in the synthesized molecules.